Analisis Dampak Keberadaan Kompleks Pendidikan Muhammadiyah Labuhan Ratu untuk Perekonomian Masyarakat - Apriani, Nining; Mawardi, Mawardi; Albab, Ulil (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
The purpose of this study was to study the Impact of the Existence of the Muhammadiyah Labuhan Ratu Education Complex on the community's economy and to find out how the level of community income changed after establishing a business in the Muhammadiyah Labuhan Ratu Education Complex. This study involved interviews with 15 business owners in the Muhammadiyah Labuhan Ratu Education Complex. This study used a descriptive qualitative method, this study involved 15 respondents who were business owners in the Muhammadiyah Labuhan Ratu Education Complex. The results of the study showed that the existence of the Muhammadiyah Education Complex significantly affected the local economy, with an increase in respondents between 30-80% in addition there was a real socio-economic change, with previously quiet areas becoming more lively with many business opportunities. Thus, the Muhammadiyah Labuhan Ratu Education Complex plays a significant role in improving the regional economy and improving the quality of life of the community.